2016
DOI: 10.1177/0091026016644625
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Performance Appraisal Justice on the Effectiveness of Pay-for-Performance Systems After Civil Service Reform

Abstract: The present study comprehensively examined how human resources (HR) directors in six U.S. state governments with drastic levels of civil service reform assess their states' pay-for-performance effectiveness in terms of the performance appraisal justice. It was found that the effectiveness of pay-for-performance is influenced by perceived fairness of performance appraisal. More specifically, this study found that perceived politicization of performance appraisal was negatively and significantly associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 55 publications
1
28
0
1
Order By: Relevance
“…Kim and Rubianty (2011) determined that perceptions of procedural fairness were associated with intrinsic motivation. Kim (2016) found that perceived unfairness in performance appraisal, especially a perceived lack of clarity in appraisal criteria and politicization of the appraisal process, had a significant relationship with the performance-based pay system's effectiveness. or improving/evaluating system performance).…”
Section: Acqdemo's Resource-intensive Naturementioning
confidence: 99%
“…Kim and Rubianty (2011) determined that perceptions of procedural fairness were associated with intrinsic motivation. Kim (2016) found that perceived unfairness in performance appraisal, especially a perceived lack of clarity in appraisal criteria and politicization of the appraisal process, had a significant relationship with the performance-based pay system's effectiveness. or improving/evaluating system performance).…”
Section: Acqdemo's Resource-intensive Naturementioning
confidence: 99%
“…A pay-forperformance system, when the increase in the civil servant's salary is related to the evaluation of his/her activity, was introduced in the civil service: when the activity is productive, and the results are betterwages increase faster, when performance is worsethey increase slower and when they are unsatisfactorywages do not increase (Brewer and Kellough, 2016). Although this system is considered more flexible, fairer and allowing for a better link between the salary of a civil servant with his performance results and motivation compared to the traditional one (Willems, Janvier and Henderickx, 2006;Rosen, 2007;Myers, 2008;Houston, 2009;Kim, 2016), however, due to the specifics of civil service activities, their complexity and multi-functionality, limited possibilities to assess the contribution of a single public civil servant to a joint activity as well as the results or their absence, the application of the pay-for-performance system in the civil service is complex, expensive, uncertain and difficult to apply (Perry, Mesch and Paarlberg, 2006;Langbein, 2010;Walther, 2015;Brewer and Kellough, 2016). According to D. Bossaert, Ch.…”
Section: Monetary Incentivesmentioning
confidence: 99%
“…The supervisor has the duty of translating the observable features in an employee workplace administration to judgmental ratings relevant and comparable across the organizations. Kim (2016), presented a study titling the effect on performance evaluation system implied to civil service performance to have a better pay. The study targeted human resource directors in the United States after civil reforms in performance appraisal of 30 state agencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employee productivity has been assessed in various studies to be affected by a number of factors. Kim (2016) noted that the level of performance evaluation influenced productivity in employees. The evaluation of employees was therefore encouraged, but caution was advised on evaluation as extreme measures of evaluation were found to border micro-management of employees that led to demotivation of employees.…”
Section: Performance Feedback and Employee Productivitymentioning
confidence: 99%